ChatGPT in Action: Unraveling its Impact on Student Motivation in English Language Learning - Jayaputri, Herlandri Eka (SCOPE: Journal of English Language Teaching, 2024)
The utilization of Natural Language Processing (NLP) technology has emerged as a valuable instrument for students due to its considerable potential in transforming the educational process. The proliferation and acceptance of AI in educational settings have garnered considerable attention from scholars, prompting comprehensive investigation. This study employs an experimental design utilizing a One Group Pretest-Posttest arrangement to assess the impact of ChatGPT on student motivation in learning the English language. The study participants comprised 40 students from the Fisheries Academy in Biak, Papua, Indonesia, selected based on criteria such as technology possession, English language proficiency, and willingness to partake. Data collection was conducted through English language proficiency assessments and questionnaires, subsequently analyzed employing SPSS 25.0 software. Results revealed a notable enhancement in student motivation subsequent to the implementation of ChatGPTin English language learning. Both English proficiency test outcomes and questionnaire responses exhibited significant elevations in student motivation from the pre-test to the post-test phase. Statistical scrutiny verified substantial disparities between pre-test and post-test scores, affirming the efficacy of ChatGPTin augmenting student motivation. Factors contributing to this elevation encompass personalized and real-time interactions, adaptive learning methodologies, and the user-friendly nature of AI technology.